Pa se sliš ... Pritrkavanje v slovenskem in evropskem prostoru - Kovačič, Mojca (Folkloristika, 2012)
The monograph deals with the musical practice of bell chiming, which is part of folk music tradition in Slovenia, as well as in some other European countries. Bell chiming is the rhythmic chiming of church bells, which is nowadays a fairly popular musical practice among the older and younger generations alike. The book is based on modern research and, where appropriate, comparatively approaches the material from a historical and geographical point of view. Apart from its musical analyses, which present structural and formational elements of bell-chiming tunes in detail, the book also discusses sociological questions, such as the role of bell chiming in the clerical and also in the secular context, the manner of musical transfer, the performativity of musical practice and the roles of the sexes in bell chiming. Bell chiming is placed within the broader context of European chiming. The detailed discussion of bell chiming in both Germany and Croatia refutes the old myth of bell chiming as a Slovenian national speciality.